The Law Commission's 1988 Report on Accident Compensation - Keith, Sir Kenneth J (Victoria University of Wellington Law Review, 2003)
As economic restructuring was changing many state functions, the New Zealand Law Commission under the Presidency of Sir Owen Woodhouse undertook its own review of ACC, vigorously reaffirming the Woodhouse principles in its 1988 Report, while proposing further extensions of the scheme. This paper, written by a member of the Commission, summarises the Report’s major recommendations, including a new strategy for accident prevention, extension of the scheme to include illness, and a generally sceptical approach to incentive-based premiums for employers.